Physiological and biochemical characteristics and microbial responses of Medicago sativa (Fabales: Fabaceae) varieties with different resistance to atrazine stress - Li, Yingao; Lu, Jiading; Dong, Chunyang; Wang, Haojie; Liu, Boshuai; Li, Defeng; Cui, Yalei; Wang, Zhichang; Ma, Sen; Shi, Yinghua; Wang, Chengzhang; Zhu, Xiaoyan; et al. (Frontiers in Microbiology, 2024)
Atrazine, a commonly employed herbicide for corn production, can leave residues in soil, resulting in photosynthetic toxicity and impeding growth in subsequent alfalfa (Medicago sativa L.) crops within alfalfa-corn rotation systems. The molecular regulatory mechanisms by which atrazine affects alfalfa growth and development, particularly its impact on the microbial communities of the alfalfa rhizosphere, are not well understood. This study carried out field experiments to explore the influence of atrazine stress on the biomass, chlorophyll content, antioxidant system, and rhizosphere microbial communities of the atrazine-sensitive alfalfa variety WL-363 and the atrazine-resistant variety JN5010. The results revealed that atrazine significantly reduced WL-363 growth, decreasing plant height by 8.58 cm and root length by 5.42 cm (P < 0.05). Conversely, JN5010 showed minimal reductions, with decreases of 1.96 cm in height and 1.26 cm in root length. Chlorophyll content in WL-363 decreased by 35% under atrazine stress, while in JN5010, it was reduced by only 10%.Reactive oxygen species (ROS) accumulation increased by 60% in WL-363, compared to a 20% increase in JN5010 (P < 0.05 for both). Antioxidant enzyme activities, such as superoxide dismutase (SOD) and catalase (CAT), were significantly elevated in JN5010 (P < 0.05), suggesting a more robust defense mechanism. Although the predominant bacterial and fungal abundances in rhizosphere soils remained generally unchanged under atrazine stress, specific microbial groups exhibited variable responses. Notably, Promicromonospora abundance declined in WL-363 but increased in JN5010. FAPROTAX functional predictions indicated shifts in the abundance of microorganisms associated with pesticide degradation, resistance, and microbial structure reconstruction under atrazine stress, displaying different patterns between the two varieties. This study provides insights into how atrazine residues affect alfalfa rhizosphere microorganisms and identifies differential microbial responses to atrazine stress, offering valuable reference data for screening and identifying atrazine-degrading bacteria.